Cardiovascular Risk Factors and Social Development Index - Martínez-García, Mireya; Gutiérrez-Esparza, Guadalupe O.; Roblero-Godinez, Juan Carlos; Marín-Pérez, Diana Vianey; Montes-Ruiz, Cindy Lucia; Vallejo, Maite; Hernández-Lemus, Enrique (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular diseases (CVD) are the leading causes of morbidity and mortality worldwide. The complex etiology of CVD is known to be significantly affected by environmental and social factors. There is, however a lag in our understanding of how population level components may be related to the onset and severity of CVD, and how some indicators of unsatisfied basic needs might be related to known risk factors. Here we present a cross-sectional study aimed to analyze the association between cardiovascular risk factors (CVRF) and social development index (SDI) in adult individuals within a metropolitan urban environment. The six components of SDI, as well as, socioeconomic, anthropometric, clinical, biochemical and risk behavior parameters were explored within the study population. As a result, several CVRF (waist circumference, waist-to-height-ratio, body mass index, systolic blood pressure, glucose, lower high-density lipoprotein cholesterol, triglycerides and sodium) were found in a higher proportion in the low or very low levels of the SDI, and this pattern occurs more in women than in men. Canonical analysis indicates a correlation between other socioeconomic features and anthropometric, clinical, and biochemical factors (canonical coefficient = 0.8030). Further studies along these lines are needed to fully establish how to insert such associations into the design of health policy and interventions with a view to lessen the burden of cardiovascular diseases, particularly in metropolitan urban environments.